Approach of the treatment for pneumothorax - Huang, Yong; Huang, Haidong; Li, Qiang; Browning, Robert F.; Parrish, Scott; Turner, J. Francis; Zarogoulidis, Konstantinos; Kougioumtzi, Ioanna; Dryllis, Georgios; Kioumis, Ioannis; Pitsiou, Georgia; Machairiotis, Nikolaos; et al. (Journal of Thoracic Disease; Vol 6, Supplement 4 (October 10, 2014): Journal of Thoracic Disease (Pneumothorax: From Definition to Diagnosis and Treatment), 2014)
Pneumothorax can occur in several situations such as; chronic obstructive pulmonary disease (COPD) where emphysema is observed or due to a biopsy for malignancy suspicion. In any case it is a dangerous situation that requires immediate attention and treatment. Pneumothorax can be divided in primary and secondary. Staging of pneumothorax is also very important. In our current editorial we summarize etiology and treatment of pneumothorax from a panel of pulmonary physicians, oncologists and thoracic surgeons.